Soluble HLA peptidome of pleural effusions is a valuable source for tumor antigens. Issue 5 (17th May 2022) - Khazan-Kost, Sofia; Cafri, Gal; Melamed Kadosh, Dganit; Mooshayef, Navit; Chatterji, Sumit; Dominissini, Dan; Manor, Sigal; Zisser, Bracha; Broday, Limor; Talalai, Efrosiniia; Shemer, Anat; Zadok, Oranit; et al.
Abstract : Background: Soluble human leucocyte antigen (sHLA) molecules, released into the plasma, carry their original peptide cargo and provide insight into the protein synthesis and degradation schemes of their source cells and tissues. Other body fluids, such as pleural effusions, may also contain sHLA-peptide complexes, and can potentially serve as a source of tumor antigens since these fluids are drained from the tumor microenvironment. We explored this possibility by developing a methodology for purifying and analyzing large pleural effusion sHLA class I peptidomes of patients with malignancies or benign diseases. Methods: Cleared pleural fluids, cell pellets present in the pleural effusions, and the primary tumor cells cultured from cancer patients' effusions, were used for immunoaffinity purification of the HLA molecules. The recovered HLA peptides were analyzed by liquid chromatography coupled to tandem mass spectrometry (LC-MS/MS) and the resulting LC-MS/MS data were analyzed with the MaxQuant software tool. Selected tumor antigen peptides were tested for their immunogenicity potential with donor peripheral blood mononuclear cells (PBMCs) in an in vitro assay. Results: Mass spectrometry analysis of the pleural effusions revealed 39, 669 peptides attributable to 11, 305 source proteins. The majority of peptides identified from the pleural effusions were defined as HLA ligands that fit the patients' HLA consensus sequence motifs. The membranal and soluble HLA peptidomes of each individual patient correlated to each other. Additionally, soluble HLA peptidomes from the same patient, obtained at different visits to the clinic, were highly similar. Compared with benign effusions, the soluble HLA peptidomes of malignant pleural effusions were larger and included HLA peptides derived from known tumor-associated antigens, including cancer/testis antigens, lung-related proteins, and vascular endothelial growth factor pathway proteins. Selected tumor-associated antigens that were identified by the immunopeptidomics were able to successfully prime CD8 + T cells. Conclusions: Pleural effusions contain sHLA-peptide complexes, and the pleural effusion HLA peptidome of patients with malignant tumors can serve as a rich source of biomarkers for tumor diagnosis and potential candidates for personalized immunotherapy.